STUDENTS’ PERCEPTION ON THE CONTRIBUTION OF LITERATURE IN READING AND WRITING SKILLS - Rita Hermida (Getsempena English Education Journal, 2019)
For language learners, being skilled in all part of the language is priority. In order to have those skills, many ways are done by the learners. Not only the method of study, have some other fields of study also given a contribution to the learning process. Literature, as one of the fields, has a lot of contributions to the language elements and skills. All part of listening, speaking, reading and writing, including vocabulary and grammar are much contributed through studying literature. In this study, the writer was interested in conducting a deep discussion about the students’ perception on the contribution of literature in reading and writing skills. The sample of this study was 52 English Department students who had taken literature courses. The data were taken by distributing them opened-questionnaires consist of some questions about the contribution of literature in reading and writing skills which are related to their own experiences. The result shows that 8% of the students stated that literature gave a significant contribution to their writing skill only, and 25 % of them agreed that literature gave a significant contribution to their reading skill only, and 67% of them agreed that literature gave a significant contribution to both of their reading and writing skill as well.